2009
DOI: 10.1159/000265530
|View full text |Cite
|
Sign up to set email alerts
|

Topical ‘Sydney’ Propolis Protects against UV-Radiation-Induced Inflammation, Lipid Peroxidation and Immune Suppression in Mouse Skin

Abstract: Background: Propolis is a honeybee product that has been used in traditional medicine for antioxidant, immune-stimulating, anti-inflammatory and anti-cancer effects. Here, the potential of the topical application of a crude ethanolic extract of Sydney propolis to protect against UV-radiation-induced impairments associated with an increased risk of photocarcinogenesis has been tested in the hairless mouse. Methods: Solutions providing between 10 and 200 mg/kg propolis were applied to the skin following UV irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 89 publications
1
30
0
1
Order By: Relevance
“…In our findings we reported that GRNS inhibited IL-10 secretion and co-addition of propolis normalized such inhibition. The stimulation of IL-10 secretion was reported in study of Cole et al (2010) and is parallel to our findings. NS modulated TNF-α secretion but γ-irradiated NS inhibited TNF-α secretion and propolis normalized it.…”
Section: Ajbbsupporting
confidence: 92%
“…In our findings we reported that GRNS inhibited IL-10 secretion and co-addition of propolis normalized such inhibition. The stimulation of IL-10 secretion was reported in study of Cole et al (2010) and is parallel to our findings. NS modulated TNF-α secretion but γ-irradiated NS inhibited TNF-α secretion and propolis normalized it.…”
Section: Ajbbsupporting
confidence: 92%
“…Sydney propolis was able to reduce cutaneous inflammation, immunosuppression and lipid peroxidation induced by UV exposure. [76] Propolis significantly and dosedependently protected against both sunburn oedema and the suppression of contact hypersensitivity, and against lipid peroxidation. The overexpression of interleukin-10 and the depletion of interleukin-12 characteristic of photoimmune suppression were markedly reduced by propolis.…”
Section: Propolis and Experimental Carcinogenesismentioning
confidence: 90%
“…There is increased interest in the identification of natural product sources for novel anti-inflammatory and antioxidant compounds that might prove to be of superior efficacy in preventing and/or treating the skin from the photodamage [171,172]. Naturally occurring agents are considered to be less toxic and more effective approaches in controlling various human malignancies [173,174]; thus, a new concept in cosmetics research and development is the use of the so-called "biological filters," such as the potent antioxidants, vitamins, and flavonoids, which can have protective effects against UVR and may also have biologically relevant filtering activity [175].…”
Section: Development Of Topical Formulations Containing Flavonoidsmentioning
confidence: 99%
“…It has been suggested that these properties may arise from complex mechanisms or synergistic interactions between compounds [199]. The topical application of a crude de-waxed ethanolic extract of "Sydney" propolis in the Skh:hr-1 albino hairless mouse was effective in reducing inflammation, immunosuppression, and oxidative damage caused by UV exposure [171].…”
Section: Development Of Topical Formulations Containing Flavonoidsmentioning
confidence: 99%